Question
upstudy study bank question image url

B. Exercises solve and graph the solution set. \( \begin{array}{lll}\text { 15. } x^{2}<4 x+45 & \text { 16. } 6-x^{2} \leq x & \text { 17. } 3 x-1>3-x^{2} \\ \text { 18. } 16 x^{2}-9 \leq 0 & \text { 19. } x+6 \leq 2 x^{2} & \text { 20. } x^{2}-6 x+7>0 \\ \text { 21. } 12 x+3 \leq 4 x^{2} & \text { 22. } x-x^{2}<1 & \text { 23. } x^{2}+2 x>-1\end{array} \)

Ask by Crawford Love. in the United States
Jan 31,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Here are the solutions to the inequalities: 1. \( -5 < x < 9 \) 2. \( x \leq -3 \) or \( x \geq 2 \) 3. \( x < -4 \) or \( x > 1 \) 4. \( -\frac{3}{4} \leq x \leq \frac{3}{4} \) 5. \( x \leq -\frac{3}{2} \) or \( x \geq 2 \) 6. All real numbers (\( x \in \mathbb{R} \)) 7. \( x \leq \frac{-2\sqrt{3}+3}{2} \) or \( x \geq \frac{2\sqrt{3}+3}{2} \) 8. All real numbers (\( x \in \mathbb{R} \)) 9. \( x \neq -1 \) Graphs of these solution sets can be plotted on a number line to visualize the intervals where each inequality holds true.

Solution

Solve the inequality by following steps: - step0: Solve the inequality by testing the values in the interval: \(x^{2}+2x+1>0\) - step1: Rewrite the expression: \(x^{2}+2x+1=0\) - step2: Factor the expression: \(\left(x+1\right)^{2}=0\) - step3: Simplify the expression: \(x+1=0\) - step4: Move the constant to the right side: \(x=0-1\) - step5: Remove 0: \(x=-1\) - step6: Determine the test intervals: \(\begin{align}&x<-1\\&x>-1\end{align}\) - step7: Choose a value: \(\begin{align}&x_{1}=-2\\&x_{2}=0\end{align}\) - step8: Test the chosen value: \(\begin{align}&x<-1\textrm{ }\textrm{is the solution}\\&x>-1\textrm{ }\textrm{is the solution}\end{align}\) - step9: The final solution is \(x\neq -1:\) \(x\neq -1\) Solve the equation \( x-x^{2}-1<0 \). Solve the inequality by following steps: - step0: Solve the inequality by testing the values in the interval: \(x-x^{2}-1<0\) - step1: Rewrite the expression: \(x-x^{2}-1=0\) - step2: Add or subtract both sides: \(x-x^{2}=1\) - step3: Divide both sides: \(\frac{x-x^{2}}{-1}=\frac{1}{-1}\) - step4: Evaluate: \(-x+x^{2}=-1\) - step5: Add the same value to both sides: \(-x+x^{2}+\frac{1}{4}=-1+\frac{1}{4}\) - step6: Simplify the expression: \(\left(x-\frac{1}{2}\right)^{2}=-\frac{3}{4}\) - step7: The statement is false for any value of \(x:\) \(x \notin \mathbb{R}\) - step8: Choose a value: \(x=0\) - step9: Test the chosen value: \(x \in \mathbb{R}\) Solve the equation \( 16x^{2}-9\leq0 \). Solve the inequality by following steps: - step0: Solve the inequality by testing the values in the interval: \(16x^{2}-9\leq 0\) - step1: Rewrite the expression: \(16x^{2}-9=0\) - step2: Move the constant to the right side: \(16x^{2}=0+9\) - step3: Remove 0: \(16x^{2}=9\) - step4: Divide both sides: \(\frac{16x^{2}}{16}=\frac{9}{16}\) - step5: Divide the numbers: \(x^{2}=\frac{9}{16}\) - step6: Simplify the expression: \(x=\pm \sqrt{\frac{9}{16}}\) - step7: Simplify: \(x=\pm \frac{3}{4}\) - step8: Separate into possible cases: \(\begin{align}&x=\frac{3}{4}\\&x=-\frac{3}{4}\end{align}\) - step9: Determine the test intervals: \(\begin{align}&x<-\frac{3}{4}\\&-\frac{3}{4}\frac{3}{4}\end{align}\) - step10: Choose a value: \(\begin{align}&x_{1}=-2\\&x_{2}=0\\&x_{3}=2\end{align}\) - step11: Test the chosen value: \(\begin{align}&x<-\frac{3}{4}\textrm{ }\textrm{is not a solution}\\&-\frac{3}{4}\frac{3}{4}\textrm{ }\textrm{is not a solution}\end{align}\) - step12: Include the critical value: \(\begin{align}&-\frac{3}{4}\leq x\leq \frac{3}{4}\textrm{ }\textrm{is the solution}\end{align}\) - step13: The final solution is \(-\frac{3}{4}\leq x\leq \frac{3}{4}:\) \(-\frac{3}{4}\leq x\leq \frac{3}{4}\) Solve the equation \( 6-x^{2}-x\leq0 \). Solve the inequality by following steps: - step0: Solve the inequality by testing the values in the interval: \(6-x^{2}-x\leq 0\) - step1: Rewrite the expression: \(6-x^{2}-x=0\) - step2: Factor the expression: \(\left(2-x\right)\left(3+x\right)=0\) - step3: Separate into possible cases: \(\begin{align}&2-x=0\\&3+x=0\end{align}\) - step4: Solve the equation: \(\begin{align}&x=2\\&x=-3\end{align}\) - step5: Determine the test intervals: \(\begin{align}&x<-3\\&-32\end{align}\) - step6: Choose a value: \(\begin{align}&x_{1}=-4\\&x_{2}=-1\\&x_{3}=3\end{align}\) - step7: Test the chosen value: \(\begin{align}&x<-3\textrm{ }\textrm{is the solution}\\&-32\textrm{ }\textrm{is the solution}\end{align}\) - step8: Include the critical value: \(\begin{align}&x\leq -3\textrm{ }\textrm{is the solution}\\&x\geq 2\textrm{ }\textrm{is the solution}\end{align}\) - step9: The final solution is \(x \in \left(-\infty,-3\right]\cup \left[2,+\infty\right):\) \(x \in \left(-\infty,-3\right]\cup \left[2,+\infty\right)\) Solve the equation \( 3x-1-3+x^{2}>0 \). Solve the inequality by following steps: - step0: Solve the inequality by testing the values in the interval: \(3x-1-3+x^{2}>0\) - step1: Subtract the numbers: \(3x-4+x^{2}>0\) - step2: Rewrite the expression: \(3x-4+x^{2}=0\) - step3: Factor the expression: \(\left(-1+x\right)\left(4+x\right)=0\) - step4: Separate into possible cases: \(\begin{align}&-1+x=0\\&4+x=0\end{align}\) - step5: Solve the equation: \(\begin{align}&x=1\\&x=-4\end{align}\) - step6: Determine the test intervals: \(\begin{align}&x<-4\\&-41\end{align}\) - step7: Choose a value: \(\begin{align}&x_{1}=-5\\&x_{2}=-2\\&x_{3}=2\end{align}\) - step8: Test the chosen value: \(\begin{align}&x<-4\textrm{ }\textrm{is the solution}\\&-41\textrm{ }\textrm{is the solution}\end{align}\) - step9: The final solution is \(x \in \left(-\infty,-4\right)\cup \left(1,+\infty\right):\) \(x \in \left(-\infty,-4\right)\cup \left(1,+\infty\right)\) Solve the equation \( x^{2}-4x-45<0 \). Solve the inequality by following steps: - step0: Solve the inequality by testing the values in the interval: \(x^{2}-4x-45<0\) - step1: Rewrite the expression: \(x^{2}-4x-45=0\) - step2: Factor the expression: \(\left(x-9\right)\left(x+5\right)=0\) - step3: Separate into possible cases: \(\begin{align}&x-9=0\\&x+5=0\end{align}\) - step4: Solve the equation: \(\begin{align}&x=9\\&x=-5\end{align}\) - step5: Determine the test intervals: \(\begin{align}&x<-5\\&-59\end{align}\) - step6: Choose a value: \(\begin{align}&x_{1}=-6\\&x_{2}=2\\&x_{3}=10\end{align}\) - step7: Test the chosen value: \(\begin{align}&x<-5\textrm{ }\textrm{is not a solution}\\&-59\textrm{ }\textrm{is not a solution}\end{align}\) - step8: The final solution is \(-50 \). Solve the inequality by following steps: - step0: Solve the inequality by testing the values in the interval: \(x^{2}-6x+7>0\) - step1: Rewrite the expression: \(x^{2}-6x+7=0\) - step2: Add or subtract both sides: \(x^{2}-6x=-7\) - step3: Add the same value to both sides: \(x^{2}-6x+9=-7+9\) - step4: Simplify the expression: \(\left(x-3\right)^{2}=2\) - step5: Simplify the expression: \(x-3=\pm \sqrt{2}\) - step6: Separate into possible cases: \(\begin{align}&x-3=\sqrt{2}\\&x-3=-\sqrt{2}\end{align}\) - step7: Move the constant to the right side: \(\begin{align}&x=\sqrt{2}+3\\&x=-\sqrt{2}+3\end{align}\) - step8: Determine the test intervals: \(\begin{align}&x<-\sqrt{2}+3\\&-\sqrt{2}+3\sqrt{2}+3\end{align}\) - step9: Choose a value: \(\begin{align}&x_{1}=1\\&x_{2}=3\\&x_{3}=5\end{align}\) - step10: Test the chosen value: \(\begin{align}&x<-\sqrt{2}+3\textrm{ }\textrm{is the solution}\\&-\sqrt{2}+3\sqrt{2}+3\textrm{ }\textrm{is the solution}\end{align}\) - step11: The final solution is \(x \in \left(-\infty,-\sqrt{2}+3\right)\cup \left(\sqrt{2}+3,+\infty\right):\) \(x \in \left(-\infty,-\sqrt{2}+3\right)\cup \left(\sqrt{2}+3,+\infty\right)\) Solve the equation \( x+6-2x^{2}\leq0 \). Solve the inequality by following steps: - step0: Solve the inequality by testing the values in the interval: \(x+6-2x^{2}\leq 0\) - step1: Rewrite the expression: \(x+6-2x^{2}=0\) - step2: Factor the expression: \(\left(2-x\right)\left(3+2x\right)=0\) - step3: Separate into possible cases: \(\begin{align}&2-x=0\\&3+2x=0\end{align}\) - step4: Solve the equation: \(\begin{align}&x=2\\&x=-\frac{3}{2}\end{align}\) - step5: Determine the test intervals: \(\begin{align}&x<-\frac{3}{2}\\&-\frac{3}{2}2\end{align}\) - step6: Choose a value: \(\begin{align}&x_{1}=-3\\&x_{2}=0\\&x_{3}=3\end{align}\) - step7: Test the chosen value: \(\begin{align}&x<-\frac{3}{2}\textrm{ }\textrm{is the solution}\\&-\frac{3}{2}2\textrm{ }\textrm{is the solution}\end{align}\) - step8: Include the critical value: \(\begin{align}&x\leq -\frac{3}{2}\textrm{ }\textrm{is the solution}\\&x\geq 2\textrm{ }\textrm{is the solution}\end{align}\) - step9: The final solution is \(x \in \left(-\infty,-\frac{3}{2}\right]\cup \left[2,+\infty\right):\) \(x \in \left(-\infty,-\frac{3}{2}\right]\cup \left[2,+\infty\right)\) Solve the equation \( 12x+3-4x^{2}\leq0 \). Solve the inequality by following steps: - step0: Solve the inequality by testing the values in the interval: \(12x+3-4x^{2}\leq 0\) - step1: Rewrite the expression: \(12x+3-4x^{2}=0\) - step2: Add or subtract both sides: \(12x-4x^{2}=-3\) - step3: Divide both sides: \(\frac{12x-4x^{2}}{-4}=\frac{-3}{-4}\) - step4: Evaluate: \(-3x+x^{2}=\frac{3}{4}\) - step5: Add the same value to both sides: \(-3x+x^{2}+\frac{9}{4}=\frac{3}{4}+\frac{9}{4}\) - step6: Simplify the expression: \(\left(x-\frac{3}{2}\right)^{2}=3\) - step7: Simplify the expression: \(x-\frac{3}{2}=\pm \sqrt{3}\) - step8: Separate into possible cases: \(\begin{align}&x-\frac{3}{2}=\sqrt{3}\\&x-\frac{3}{2}=-\sqrt{3}\end{align}\) - step9: Solve the equation: \(\begin{align}&x=\frac{2\sqrt{3}+3}{2}\\&x=\frac{-2\sqrt{3}+3}{2}\end{align}\) - step10: Determine the test intervals: \(\begin{align}&x<\frac{-2\sqrt{3}+3}{2}\\&\frac{-2\sqrt{3}+3}{2}\frac{2\sqrt{3}+3}{2}\end{align}\) - step11: Choose a value: \(\begin{align}&x_{1}=-1\\&x_{2}=2\\&x_{3}=4\end{align}\) - step12: Test the chosen value: \(\begin{align}&x<\frac{-2\sqrt{3}+3}{2}\textrm{ }\textrm{is the solution}\\&\frac{-2\sqrt{3}+3}{2}\frac{2\sqrt{3}+3}{2}\textrm{ }\textrm{is the solution}\end{align}\) - step13: Include the critical value: \(\begin{align}&x\leq \frac{-2\sqrt{3}+3}{2}\textrm{ }\textrm{is the solution}\\&x\geq \frac{2\sqrt{3}+3}{2}\textrm{ }\textrm{is the solution}\end{align}\) - step14: The final solution is \(x \in \left(-\infty,\frac{-2\sqrt{3}+3}{2}\right]\cup \left[\frac{2\sqrt{3}+3}{2},+\infty\right):\) \(x \in \left(-\infty,\frac{-2\sqrt{3}+3}{2}\right]\cup \left[\frac{2\sqrt{3}+3}{2},+\infty\right)\) Let's solve and graph the solution sets for each inequality step by step. ### 15. \( x^{2} < 4x + 45 \) Rearranging gives: \[ x^{2} - 4x - 45 < 0 \] Factoring: \[ (x - 9)(x + 5) < 0 \] The critical points are \( x = -5 \) and \( x = 9 \). Testing intervals: - For \( x < -5 \): Choose \( x = -6 \) → Positive - For \( -5 < x < 9 \): Choose \( x = 0 \) → Negative - For \( x > 9 \): Choose \( x = 10 \) → Positive Thus, the solution is: \[ -5 < x < 9 \] ### 16. \( 6 - x^{2} \leq x \) Rearranging gives: \[ -x^{2} - x + 6 \leq 0 \quad \Rightarrow \quad x^{2} + x - 6 \geq 0 \] Factoring: \[ (x - 2)(x + 3) \geq 0 \] The critical points are \( x = -3 \) and \( x = 2 \). Testing intervals: - For \( x < -3 \): Positive - For \( -3 < x < 2 \): Negative - For \( x > 2 \): Positive Thus, the solution is: \[ x \in (-\infty, -3] \cup [2, +\infty) \] ### 17. \( 3x - 1 > 3 - x^{2} \) Rearranging gives: \[ x^{2} + 3x - 4 > 0 \] Factoring: \[ (x - 1)(x + 4) > 0 \] The critical points are \( x = -4 \) and \( x = 1 \). Testing intervals: - For \( x < -4 \): Positive - For \( -4 < x < 1 \): Negative - For \( x > 1 \): Positive Thus, the solution is: \[ x \in (-\infty, -4) \cup (1, +\infty) \] ### 18. \( 16x^{2} - 9 \leq 0 \) Rearranging gives: \[ (4x - 3)(4x + 3) \leq 0 \] The critical points are \( x = -\frac{3}{4} \) and \( x = \frac{3}{4} \). Testing intervals: - For \( x < -\frac{3}{4} \): Positive - For \( -\frac{3}{4} < x < \frac{3}{4} \): Negative - For \( x > \frac{3}{4} \): Positive Thus, the solution is: \[ -\frac{3}{4} \leq x \leq \frac{3}{4} \] ### 19. \( x + 6 \leq 2x^{2} \) Rearranging gives: \[ 2x^{2} - x - 6 \geq 0 \] Factoring: \[ (2x + 3)(x - 2) \geq 0 \] The critical points are \( x = -\frac{3}{2} \) and \( x = 2 \). Testing intervals: - For \( x < -\frac{3}{2} \): Positive - For \( -\frac{3}{2} < x < 2 \): Negative - For \( x > 2 \): Positive Thus, the solution is: \[ x \in (-\infty, -\frac{3}{2}] \cup [2, +\infty) \] ### 20. \( x^{2} - 6x + 7 > 0 \) The discriminant is negative: \[ (-6)^{2} - 4 \cdot 1 \cdot 7 = 36 - 28 = 8 > 0 \] Thus, the quadratic does not cross the x-axis and opens upwards. Therefore, it is always positive: \[ x \in \mathbb{R} \] ### 21. \( 12x + 3 \leq 4x^{2} \) Rearranging gives: \[ 4x^{2} - 12x - 3 \geq 0 \] Using the quadratic formula: \[ x = \frac{12 \pm \sqrt{144 + 48}}{8} = \frac{12 \pm 6\sqrt{3}}{8} = \frac{3 \pm \frac{3\sqrt{3}}{2}}{2} \] Thus, the solution is: \[ x \in (-\infty, \frac{-2\sqrt{3}+3}{2}] \cup [\frac{2\sqrt{3}+3}{2}, +\infty) \] ### 22. \( x - x^{2} < 1 \) Rearranging gives: \[ -x^{2} + x - 1 < 0 \quad \Rightarrow \quad x^{2} - x + 1 > 0 \] The discriminant is negative: \[ (-1)^{2} - 4 \cdot 1 \cdot 1 = 1 - 4 = -3 < 0 \] Thus, the quadratic is always positive: \[ x \in \mathbb{R} \] ### 23. \( x^{2} + 2x > -1 \) Rearranging gives: \[ x^{2} + 2x + 1 > 0 \quad \Rightarrow \quad (x + 1)^{2} > 0 \] This is true for all \( x \neq -1 \): \[ x \neq -1 \] ### Summary of Solutions 1. \( -5 < x < 9 \) 2. \( x \in (-\infty, -3] \cup [2, +\infty) \) 3. \( x \in (-\infty, -4) \cup (1, +\infty) \) 4. \( -\frac{3}{4} \leq x \leq \frac{3}{4} \) 5. \( x \in (-\infty, -\frac{3}{2}] \cup [2, +\infty) \) 6. \( x \in \mathbb{R} \) 7. \( x \in (-\infty, \frac{-2\sqrt{3}+3}{2}] \cup

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

Let's dive into the world of inequalities! Solving these expressions isn't just about getting the answer—it's like unveiling the hidden traits of numbers! Each one depicts a storyline of relationships between x and constants. As we graph them, we visualize how values of x can weave together into harmonious or chaotic outcomes! For instance, when dealing with inequalities such as \( 15. x^{2}<4 x+45 \), we transform it into a standard form, \( x^2 - 4x - 45 < 0 \), and factor it to find critical points. By testing intervals between roots to see where the inequality holds true, we can easily sketch a graph! While completing this mini-math adventure, watch out for mistakes like flipping the inequality sign when multiplying or dividing by a negative number, which could lead you on a wild goose chase! Graphs give us such a vivid overview, but watching for signs and interval testing is our compass through this inequality forest! 🧭 Keep those tips close as you venture deeper!

Related Questions

ISCELÁNEA cribir, por simple inspección, el resultado de: \( \begin{array}{lll}(x+2)^{2} & \text { 14. }(x+y+1)(x-y-1) & \text { 27. }\left(2 a^{3}-5 b^{4}\right)^{2} \\ (x+2)(x+3) & \text { 15. }(1-a)(a+1) & \text { 28. }\left(a^{3}+12\right)\left(a^{3}-15\right) \\ (x+1)(x-1) & \text { 16. }(m-8)(m+12) & \text { 29. }\left(m^{2}-m+n\right)\left(n+m+m^{2}\right) \\ (x-1)^{2} & \text { 17. }\left(x^{2}-1\right)\left(x^{2}+3\right) & \text { 30. }\left(x^{4}+7\right)\left(x^{4}-11\right) \\ (n+3)(n+5) & \text { 18. }\left(x^{3}+6\right)\left(x^{3}-8\right) & \text { 31. }(11-a b)^{2} \\ (m-3)(m+3) & \text { 19. }\left(5 x^{3}+6 m^{4}\right)^{2} & \text { 32. }\left(x^{2} y^{3}-8\right)\left(x^{2} y^{3}+6\right) \\ (a+b-1)(a+b+1) & \text { 20. }\left(x^{4}-2\right)\left(x^{4}+5\right) & \text { 33. }(a+b)(a-b)\left(a^{2}-b^{2}\right) \\ (1+b)^{3} & \text { 21. }(1-a+b)(b-a-1) & \text { 34. }(x+1)(x-1)\left(x^{2}-2\right) \\ \left(a^{2}+4\right)\left(a^{2}-4\right) & \text { 22. }\left(a^{x}+b^{n}\right)\left(a^{x}-b^{n}\right) & \text { 35. }(a+3)\left(a^{2}+9\right)(a-3) \\ \left(3 a b-5 x^{2}\right)^{2} & \text { 23. }\left(x^{a+1}-8\right)\left(x^{a+1}+9\right) & \text { 36. }(x+5)(x-5)\left(x^{2}+1\right) \\ (a b+3)(3-a b) & \text { 24. }\left(a^{2} b^{2}+c^{2}\right)\left(a^{2} b^{2}-c^{2}\right) & \text { 37. }(a+1)(a-1)(a+2)(a-2) \\ (1-4 a x)^{2} & \text { 25. }(2 a+x)^{3} & \text { 36. }\left(x^{2}-11\right)\left(x^{2}-2\right)\end{array} \) \( \left(a^{2}+8\right)\left(a^{2}-7\right) \)
Algebra Mexico Feb 26, 2025
Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy